Olfactory bulbectomy induces neurobiological alterations in the prefrontal cortex and hyperlocomotion in male rats - Mario Alberto Bautista-Carro; Patricia Sánchez-Teoyotl; Daniel Juárez-Serrano; Tommaso Iannitti; Alfonso Díaz; Gonzalo Flores; Julio César Morales-Medina (PLoS ONE, 2026)
Major depressive disorder (MDD) is a leading cause of disability and encompasses various subtypes, including agitated depression which is associated with psychomotor agitation and elevated suicide risk. Although the olfactory bulbectomy (OBX) model has been extensively utilized to study depression-related behaviors, most studies have focused on the hippocampus, leaving the role of the prefrontal cortex (PFC) less explored. In this study, we examined the behavioral responses to novelty in the open field test and examined glial and neuronal alterations in the PFC of OBX rats. Our findings revealed that OBX induced hyperlocomotion, consistent with agitated depression. At the cellular level, OBX selectively increased the number of glial fibrillary acidic protein (GFAP)-positive astrocytes in the PFC. These modifications were accompanied by elevated nitric oxide (NO) levels, enhanced c-Fos expression, and a reduction in pyramidal neuron spine density. These findings represent the first integrated evidence of concurrent glial proliferation, NO dysregulation, and impaired neuronal plasticity in the PFC following OBX. Collectively, our results highlight the translational relevance of OBX as a model of agitated depression and point to astrocytic dysfunction and glial-neuronal interaction in the PFC as key contributors to synaptic and behavioral abnormalities in MDD.